The Mediating Role of Emotional Flexibility between Social Support and Life Satisfaction - Caglar, Azmi; Akyil, Yusuf; Ime, Yakup; Erdinc, Beste (ODTU- AYNA Klinik Psikoloji Destek Unitesi, 2025)
The purpose of this study is to examine the possible mediating role of emotional flexibility in the relationship between life satisfaction and social support among university students. A total of 344 university students, 217 female and 127 male, participated in the study. Life Satisfaction Scale, Emotional Flexibility Scale and Multidimensional Perceived Social Support Scale were used in the data collection process. Normality, descriptive statistics, reliability and correlation analyses were used to analyse the data. In addition, SEM (Structural Equation Modelling) and bootstrapping method were used in the analysis of the data. The findings of the study show that there is a positive correlation between social support, emotional resilience and life satisfaction. In addition, according to the results of this study, emotional flexibility has a partial mediating role in the relationship between social support and life satisfaction. In addition, it was determined that the increase in the level of social support positively affected both emotional flexibility and life satisfaction of university students. This situation reveals that social support has a direct effect on life satisfaction and makes a significant contribution to students' psychological wellbeing.
Keywords: emotional; flexibility; social support; life satisfaction; STRATEGIES; IMPACT; SCALE; MOOD; Psychology